Differential Expression of Inflammation-Related Genes in Children with Down Syndrome - Cláudia Regina Santos Silva; Joice Matos Biselli-Périco; Bruna Lancia Zampieri; Wilson Araujo Silva; Jorge Estefano Santana de Souza; Matheus Carvalho Bürger; Eny Maria Goloni-Bertollo; Érika Cristina Pavarino (Hindawi Limited, 2016)
Objective. The aim of the study was to investigate the expression patterns of a specific set of genes involved in the inflammation process in children with Down Syndrome (DS) and children without the syndrome (control group) to identify differences that may be related to the immune abnormalities observed in DS individuals. Method. RNA samples were obtained from peripheral blood, and gene expression was quantified using the TaqMan® Array Plate Human Inflammation Kit, which facilitated the investigation into 92 inflammation-related genes and four reference genes using real-time polymerase chain reaction (qPCR). Results. Twenty genes showed differential expression in children with DS; 12 were overexpressed (PLA2G2D, CACNA1D, ALOX12, VCAM1, ICAM1, PLCD1, ADRB1, HTR3A, PDE4C, CASP1, PLA2G5, and PLCB4), and eight were underexpressed (LTA4H, BDKRB1, ADRB2, CD40LG, ITGAM, TNFRSF1B, ITGB1, and TBXAS1). After statistically correcting for the false discovery rate, only the genes BDKRB1 and LTA4H showed differential expression, and both were underexpressed within the DS group. Conclusion. DS children showed differential expression of inflammation-related genes that were not located on chromosome 21 compared with children without DS. The BDKRB1 and LTA4H genes may differentiate the case and control groups based on the inflammatory response, which plays an important role in DS pathogenesis.